Comprehensive Analysis of the Correlation Between Pyroptosis-Related LncRNAs and Tumor Microenvironment, Prognosis, and Immune Infiltration in Hepatocellular Carcinoma - Qu, Guangzhen; Wang, Dong; Xu, Weiyu; Guo, Wei (Frontiers in Genetics, 2022)
Abstract Background: Accumulating evidence shows that pyroptosis plays a crucial role in hepatocellular carcinoma (HCC). However, the relationship between pyroptosis-related long non-coding RNAs (lncRNAs) and HCC tumor characteristics remains unclear. We aimed to explore the predictive effect of pyroptosis-related lncRNAs (PRLs) in the prognosis of HCC. Methods: We comprehensively analyzed the role of the PRLs in the tumor microenvironment and HCC prognosis by integrating genomic data from patients of HCC. Consensus clustering analysis of PRLs was applied to identify HCC subtypes. A prognostic model was then established with a training cohort from The Cancer Genome Atlas (TCGA) using univariate and least absolute shrinkage and selection operator (LASSO) Cox regression analysis. Further, we evaluated the accuracy of this predictive model using a validation set. Results: Based on pyroptosis-related lncRNAs (PRLs), a prognostic risk signature composed of seven PRLs (MKLN1AS, AL031985.3, SNHG4, GHRLOS, AC005479.2, AC099850.4, and AC026412.3) was established. For long-term prognosis of HCC patients, our model shows excellent accuracy to forecast overall survival of HCC individuals both in training set and testing set. We divided HCC patients into high and low risk groups based on median values of PRLs. Patients in the high-risk group had tumor characteristics associated with progression such as aggressive pathological grade and stage. HCC patients in the low-risk group had lower half inhibitory concentrations (IC50) for the small molecule drug sorafenib and AKT inhibitors as well as better prognosis. Conclusion: The PRLs play a crucial role in HCC carcinogenesis and progression. Our study provides strong evidence for individualized prediction of prognosis, sheds light on immunotherapy in HCC patients, and provides guidance for targeted small-molecule drug development for HCC.